3x + 5 (first plug in 2 for x )
3(2) + 5 =
6 + 5 = 11
Hope this helps . Give brainliest
Answer:
has it gone expired
Step-by-step explanation:
Answer:
<h2>3 + 4(n - 1)</h2>
Step-by-step explanation:
let r be the common differenc of the sequence
Term 12 - Term 7 = (12 - 7)r
then
47 - 27 = 5r
then
20 = 5r
then
r = 4
term 7 = term 1 + (7 - 1)r
then
27 = term 1 + 6r = term 1 + 24
then
Term1 = 27 - 24 = 3
<em><u>therefore </u></em>
the standard explicit formula of the sequence is :
term 1 + (n - 1)r = 3 + 4(n - 1)